Mycobacteria Bovis osteomyelitis following intravesical BCG for bladder cancer. (2017) - Seegobin, Karan; Maharaj, Satish; Baldeo, Cherisse; Isache, Carmen; Gharia, Bharatsinh; Zuberi, Lara
Abstract: Mycobacteria Bovis osteomyelitis is a rare adverse effect after Bacillus Calmette-Guerin (BCG) intravesical therapy. A 62-year-old male presented with acute spinal cord compression three months after completing his second course of therapy for bladder cancer. The first course with intravesical BCG was complicated with an episode of hematuria. He reported intermittent subjective fever for 3 weeks thereafter which resolved with Tylenol. Interferon-α2 B was added to the second cycle of intravesical BCG with the indication here being residual tumor, and was tolerated well. His complete blood count and liver function tests were unremarkable on admission. MRI showed features of osteomyelitis with cord compression at T4/T5. Biopsy of the affected bone showed caseating granuloma which was positive for acid fact bacilli, later confirmed to be Mycobacterium Bovis by PCR and pyrazinamide resistance. He was started on intravenous steroids and underwent spinal cord decompression. Rifampin, Isoniazid, and Ethambutol were then commenced. His weakness improved and after two months of therapy he was asymptomatic and back to his baseline function. Osteomyelitis is a rare but serious complication. Early diagnosis and treatment is important as the outcomes are good.